Productivity, nutrient uptake, and soil fertility status of acidic soil as influenced by organic amendments and inorganic nutrients applied in rainfed maize (Zea mays L.) - JAMAKHANDI, HUCHCHAPPA; DHAR, SHIVA; RATHORE, S.S.; DEVI, O.R.; SONNAD, PRAKASH; KUMAR, NAVNEET; YADAV, CHANDRAKANT; S.J., RAGHAVENDRA; JHONSONRAJU, SANKATI (Journal of Soil and Water Conservation, 2026)
A full fledge experiment was conducted at ICAR–Indian Agricultural Research Institute in Assam, during the Kharif season, 2023–2024 to appraise the impact of organic amendments and inorganic nutrients on kernel yield, nutrient uptake as well as soil fertility in rainfed maize. The study was laid out in split-plot design with three organic inputs viz; control (no input), farmyard manure (FYM) at 10 t ha-1 and vermicompost (VC) at 2.5 t ha-1 at main plot treatments and four levels of inorganic fertilizers viz; control, 50%, 75%, and 100% RDF of NPK fertilizers, each combined with lime at 300 kg per hectare under subplot treatments. Results revealed that FYM at 10 t ha-1 outperformed other treatments in nitrogen (N), phosphorus (P), and potassium (K) uptake in kernel and stover, as well as total nutrient uptake except the treatment applied with VC at 2.5 t ha-1. FYM also improved soil nutrient availability, with a magnitude of 12.06% (N), 5.35% (P), and 11.7% (K) higher over the control treatment. In addition, FYM also led to the highest microbial activity indicators: microbial biomass carbon (MBC) (199.03 μg C/g), dehydrogenase activity (DHA) (6.04 μg TPF/g/hour), and fluorescein diacetate activity (FDA) (2.92 μg fluorescein/g/hour). Among inorganic treatments, the application of 100% RDF with lime at 300 kg ha-1 significantly boosted N, P, and K uptake in kernel and stover, as well as total nutrient uptake compared to other treatments, though it was on par with 75% RDF + lime at 300 kg ha-1 for nitrogen uptake in stover. This treatment also improved soil available nutrients—18.9% (N), 9.4% (P), and 18.1% (K) higher than the control and recorded the highest microbial activity: MBC (210.80 μg C/g), DHA (6.39 μg TPF/g/ hr), and FDA (3 μg fluorescein/g/hr). Vermicompost under organic supplementation and 75% RDF + lime @ 300 kg ha-¹ under inorganic nutrient management enhanced kernel yield by 26.6% and 26.4%, respectively, over the control. The combination of FYM at 10 t ha-1 with 100% RDF + lime yielded the highest kernel output at 4.84 t ha-1. Thus, for the Northeastern region of Assam, either FYM at 10 t ha-1 or 100% RDF + lime individually enhanced nutrient uptake and soil fertility, while their integrated use was most effective in maximizing kernel yield.